Tongue Atrophy and Myopathy Mimicking EMG Findings in a Case with Acethylcholine Receptor-Positive Myasthenia Gravis - Asan, Furkan; Tütüncü, Melih; Gündüz, Ayşegül; Uzun Adatepe, Nurten (Cerrahpaşa Medical Journal, 2021)
Myasthenia gravis has various clinical presentations and can mimic multiple diseases. Isolated oro-facial muscle weakness and tongue atrophy at the time of presentation are rare. Besides the clinical picture, electrodiagnostic findings also can mimic various conditions and cause diagnostic difficulties. Our patient was a 28-year-old female admitted with non-fluctuating, progressive fatigue while talking and difficulty in swallowing. Her examination revealed tongue atrophy and fasciculations, ptosis, and facial weakness. Repetitive nerve stimulation revealed decrement in two muscle-nerve pairs. Electromyography demonstrated low amplitude and polyphasic motor unit action potentials at facial and neck muscles. She was diagnosed as having myasthenia gravis and was treated with pyridostigmine and methylprednisolone. Our case demonstrates that myasthenia gravis can present with tongue atrophy with fasciculations, oro-facial weakness, and electromyography findings mimicking myopathy. All these features were separately described during the disease course but our patient showed these features at presentation time. Repetitive nerve stimulation was the hallmark in correct diagnosis. Asetilkolin Reseptör Antikoru Pozitif Bir Miyastenia Gravis Hastasında Dil Atrofisi ve Miyopatiyi Taklit Eden EMG Bulguları Myastenia gravis farklı klinik başvuru sebeplerine sahiptir ve birçok farklı hastalığı taklit edebilir. Başvuru sırasında izole oro-fasyal kas güçsüzlüğü ve dil atrofisi nadirdir. Klinik tablonun yanında, elektrofizyolojik bulguların da farklı durumları taklit edebilmesi nedeniyle tanıda zorluklar barındırmaktadır. Bizim hastamız dalgalanma göstermeyen, giderek artan kolay yorulma ve yutma güçlüğü nedeniyle başvuran 28 yaşında kadın hastaydı. Muayenesinde dilde atrofi ve fasikülasyon ile birlikte pitoz ve fasyal güçsüzlük saptandı. Repetetif sinir uyarımı ile iki kas-sinir çiftinde dekrement yanıt elde edildi. Elektromiyografik (EMG) incelemede yüzde ve boyun kaslarında düşük amplitütlü polifazik motor ünitesi aksiyon potansiyelleri elde edildi. Myastenia gravis tanısı konan hasta piridostigmin ve metilprednizolon ile tedavi edildi. Hastamız; myasthenia gravisin dilde atrofi ile birlikte fasikülasyon, oro-fasyal güçsüzlük ve miyopatiyi taklit eden EMG bulguları ile başvurabileceğini göstermektedir. Tüm bu bulgular hastalık seyri sırasında tanımlanmış olmakla birlikte hastamız tüm bu farklı özellikleri başvuru sırasında göstermekteydi. Repetetif sinir uyarım testi doğru tanıda esas yeri teşkil etmekteydi. Cite this article as: Asan F, Tütüncü M, Gündüz A, Adatepe N. Tongue atrophy and myopathy mimicking EMG findings in a case with acethylcholine receptor-positive myasthenia gravis. Cerrahpaşa Med J. 2022;46(1):75-77.